Shigeo Satomura: 60 years of Doppler ultrasound in medicine. Issue 1 (December 2015) - Coman, Ioan; Popescu, Bogdan
Abstract This year we celebrate 60 years since Shigeo Satomura published the first measurements of the Doppler shift of ultrasonic signals from a beating heart. He demonstrated that Doppler signals can be retrieved from heart movements when insonated with 3 MHz ultrasonic waves. Later, togheter with Ziro Kaneko, he constructed the first Doppler flowmeter to measure the blood flow velocities in peripheral and extracranial brain-supplying vessels using ultrasounds. They proved that ultrasonic Doppler signals from arteries and veins can be recorded from the surface of the skin and pioneered transcutaneous flow analysis in systole and diastole in both normal and diseased blood vessels. These were the first medical applications of Doppler sonography and impressive technologic innovations have been continuing ever since. Over time, Doppler techniques became a key player in diagnostic ultrasound for hemodynamic assessment, replacing cardiac catheterization in many clinical settings.